Reconciling Trends of Mean Trophic Index and Mean Temperature of the Catch in the Eastern Mediterranean and Black Seas - KESKIN, ÇETIN; PAULY, DANIEL (Mediterranean Marine Science, 2018)
The mean trophic level, i.e., the Mean Trophic Index (MTI) and Mean Temperature of the Catch (MTC) were estimated for Turkish waters in the Eastern Mediterranean and the Black Sea based on the reconstructed marine fisheries catches (consisting of N = 88 species and/or higher taxa) of in Turkish waters for the year 1950 to 2010. The MTI decreased in both regions of Turkey, following expectations, but the MTC showed different trends in these two regions. It increased (by 0.48 °C·decade-1), along with the SST in the Eastern Mediterranean, while it fluctuated in the Black Sea. This fluctuating behaviour, however, was similar to the fluctuating tendency of SST in the Black Sea. This suggests that the MTI and MTC can be relied upon as indicators of fisheries impacts on ecosystems, and of the impact of changing temperatures on fisheries, respectively.